STUDY ON THE EFFECTS OF DIGITISATION IN SMALL AND MEDIUM-SIZED GERMAN COMPANIES - Sargut, Deniz Kerem (Calitatea, 2019)
The Digital Age has only just begun to change how we work. As the digital transformation redefines business, digitization (Digitization) represents a special challenge for businesses in general and for small and medium sized companies (SmEs) in particular. This paper will provide for an insight into and the premise for an upcoming study regarding the awareness, readiness and the capability of German SME to meet this challenge by taking into account their operational processes. It will also introduce the reader to the issues German SMEs deal with when preparing to join the wave of Digitization, Big Data Analytics (BDA), Machine Learning (ML) and Artificial Intelligence (AI). The research presented in this paper was undertaken in order to answer the question whether German SMEs are ready for the upcoming challenges and the competition in the worldwide market. A first sign of the heavy interest for Digitization from the SME market was revealed during a short telephone interview which initiated the idea for a survey. The survey showed that nearly all queried SMEs are interested in the subject of Digitization, BDA, ML and/or AI and are willing to implement these innovative facilitators in their (daily) business models through e.g. bots and/or voice-operated machines. Nevertheless, even if there is the will in the market for the implementation of these innovations, it seems as if it - for a high proportion of German SMEs - will not be possible, due to insufficient funds, lack of work force and/or work culture to fully reap the benefits or even lay the fundament of these innovations. The survey also brought to light that, in terms of a company's readiness, there is a huge disparity on a cross-departmental level in one and the same SME; while the marketing department might e.g. be ready and set-up with all necessary systems and datasets, the production department is not at all or vice versa. Therefore, it can be anticipated that even if all market participants want to join the 'lively debate' and be part of it, the actual readiness for subjects such as Digitization, BDA, ML and KI in German SMEs is still on ground zero and will involuntarily be on the agenda for the majority of these enterprises for the next ten to fifteen years.